A critical look at the notion 'pro-form'. Evidence from indexical markers, spoken discourse and (French) child language. (March 2016) - Cornish, Francis; Salazar Orvig, Anne
Abstract: The notion and term 'pro-form' are widely used in current Linguistics, in particular in studies of anaphora. They represent a generalisation based on the etymology of the term 'pronoun', extended thereby to 'pro-verbs', 'pro-VPs', 'pro-NPs', 'pro-APs' and 'pro-sentences'. The conception underlying such a usage is evidently that of the substitution of some already-mentioned textual expression by an attenuated expression (the 'pro-form'), thereby avoiding a redundant repetition of the antecedent expression at that point in the evolving co-text. The present article's goal is to show that this account is inaccurate as well as misleading as a representation of what actually goes on in extended texts, by focusing on three areas of investigation: first, a characterisation of the range of indexicals purportedly operating as 'pro-forms', together with the three major types of indexical referring procedure which they help to realise (anaphora, deixis and 'anadeixis'); next, a study of their functioning in adult unplanned interactive spoken discourse; and finally, a brief survey of the acquisition of certain French indexicals by very young children. The article proposes an alternative conception of indexical reference in discourse. Highlights: The standard notion of 'pro-forms' reflects a bias towards written language. Yet unplanned spoken and early (French) child discourse reveal a different picture. Replacing a 'pro-form' by its textual antecedent would result in incoherence. Indexicals are sui generis, not empty shells substituting their textual antecedents. Each performs specific cognitive-interactive functions in the ongoing discourse.